Application of Medicinal Plants in Maternal Healthcare and Infertility: A South African Perspective - Abdillahi, Halima S.; Van Staden, Johannes (Planta Medica, 2013)
Plants have played significant roles as medicine during pregnancy, birth, and postpartum care in many rural areas of the world. In addition to this, plants have been used for centuries to treat infertility and related reproduction problems. The aim of this paper was to review the current status of plant species used in maternal healthcare, including infertility, in South Africa, in terms of scientific evaluation for efficacy and safety. In addition to this, the role of medicinal plants as a tool in achieving the MDG5 of reducing maternal mortality by 2015 was evaluated. A search was done with the aid of Google Scholar, PubMed, Science Direct, peer-reviewed papers, and books, using keywords such as child birth, labour pain, maternal health, maternal mortality, menstrual pains, and postpartum. The plants listed in the different research articles were classified according to their use and the target effect of a plant extract or compound on reproductive function. Eighty-four plant species were found to be used to treat infertility and related problems. Twenty plant species are used during pregnancy, while 26 plant species are used to ease childbirth. For postpartum healing and any problems after childbirth, nine plant species were recorded. Unhealthy pregnancy and birth complications are among the factors that contribute to the loss of cognitive potential in the developing worldʼs children, condemning them to impoverished lives. The best way to keep a country poor is to rob its children of their full developmental potential. In this respect, medicinal plants play a significant role in reducing maternal mortality and ensuring the birth of healthy children.
Keywords: infertility; maternal healthcare; medicinal plants; South Africa; traditional medicine; woman reproductive health